Some Physical Properties of Acha (Digitaria exilis) Relevant in Mechanical Dehulling and Cleaning - Itodo, I. N.; Yusuf, P. O.; Kaankuka, T. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The properties of acha (Digitaris exilis) are important in the development off efective machines for dehulling and cleaning of the paddy. In this study, some of the relevant crop properties were determined, such as; moisture content, length, width, thickness, size and shape, arithmetic, geometric and equivalent mean diameters, surface area, volume and a thousand weight. Others includes; bulk and solid densities, porosity, angle of repose and coefficient of static friction. The fineness modulus, uniformity coefficient, particle size distribution and terminal velocity were determined for both paddy acha and grains. The properties were determined using standard methods at the moisture content of 10.3% (db) in replicates. The results showed that the length, width, thickness, size of grain, flatness index, thousand grain weight, angle of repose, angle of internal friction, bulk and solid densities were 1.58 mm, 0.90 mm, 0.76 mm, 1.58 mm, 1.65, 0.53g, 24.7o, 0.46o, 608.01 kg m-3 and 1131.0 kg m-3 respectively. The terminal velocity, porosity, coefficient of static friction, arithmetic and geometrical mean, equivalent diameters, surface area, volume, fineness modulus (paddy), fineness modulus (grain), particle size distribution (grain), particle size distribution (paddy), uniformity coefficient (grain), uniformity coefficient (paddy) was 3.96 m s-1, 46.24, 0.459, 1.127 mm, 1.859 mm, 1.059 mm, 3.36 mm², 3.00 mm3, 3.17, 3.00, 0.34, 0.36, 0.63 and 0.60 respectively. Thus, the acha (paddy and grains) can be classified as medium size and spherical in shape. In the sieve analysis of the paddy acha, 99.57 % of the paddy was retained on 0.351 mm mesh while 27.27 % and 61.72 % of the grains were retained on the 0.894 and 0.351 mm meshes. This is indicative of more variability in the grains than in the paddy. The properties show that the paddy separates easily and the grains are easily cleaned from contaminants.